BLOCKCHAIN TECHNOLOGY TRANSFORMATION IN THE E-COMMERCE MARKETING STRATEGY OF SMeS - Halek Mu'min; Sachin Vedpathak (PT. Intelek Cendikiawan Nusantara, 2025)
This research aims to identify the influence of blockchain technology transformation in the e-commerce marketing strategy of MSMEs in Bengkulu City. Blockchain has transformed e-commerce by improving transaction security, operational transparency, and efficiency. This technology builds consumer trust and increases customer loyalty. The decentralized characteristics of blockchain create a more open digital marketplace, reducing dependence on traditional intermediaries. This research uses quantitative methodology with a survey technique to collect data from SMEs in Bengkulu City. The implementation of blockchain in e-commerce not only improves security and transparency but also strengthens consumer relationships and builds an innovative and secure brand image. This study highlights the importance of risk transparency in increasing consumer trust and the effectiveness of marketing strategies